I can't make this up : life lessons - Hart, Kevin, 1979-; Strauss, Neil (37 Ink, Atria, 2017)
Superstar, comedian and Hollywood box-office star Kevin Hart turns his immense talent to the written word by writing some words. Some of those words include, the, a, for, above, and even even. Put them together and listeners have the funniest, most heartfelt, and most inspirational memoir on survival, success, and the importance of believing in themselves since Old Yeller.